Ba-filled Ni–Sb–Sn based skutterudites with anomalously high lattice thermal conductivity12. Issue 27 (21st June 2016) - Paschinger, W.; Rogl, G.; Grytsiv, A.; Michor, H.; Heinrich, P. R.; Müller, H.; Puchegger, S.; Klobes, B.; Hermann, R. P.; Reinecker, M.; Eisenmenger-Sitter, Ch.; Broz, P.; et al.
Abstract : Novel filled skutterudites Ba y Ni4 Sb12− x Sn x ( y max = 0.93) have been prepared and thoroughly characterized, which show anomalously high lattice thermal conductivity. Abstract : Novel filled skutterudites Ba y Ni4 Sb12− x Sn x ( y max = 0.93) have been prepared by arc melting followed by annealing at 250, 350 and 450 °C up to 30 days in vacuum-sealed quartz vials. Extension of the homogeneity region, solidus temperatures and structural investigations were performed for the skutterudite phase in the ternary Ni–Sn–Sb and in the quaternary Ba–Ni–Sb–Sn systems. Phase equilibria in the Ni–Sn–Sb system at 450 °C were established by means of Electron Probe Microanalysis (EPMA) and X-ray Powder Diffraction (XPD). With rather small cages Ni4 (Sb, Sn)12, the Ba–Ni–Sn–Sb skutterudite system is perfectly suited to study the influence of filler atoms on the phonon thermal conductivity. Single-phase samples with the composition Ni4 Sb8.2 Sn3.8, Ba0.42 Ni4 Sb8.2 Sn3.8 and Ba0.92 Ni4 Sb6.7 Sn5.3 were used to measure their physical properties, i.e. temperature dependent electrical resistivity, Seebeck coefficient and thermal conductivity. The resistivity data demonstrate a crossover from metallic to semiconducting behaviour. The corresponding gap width was extracted from the maxima in the Seebeck coefficient data as a function of temperature. Single crystal X-ray structure analyses at 100, 200 and 300 K revealed the thermal expansion coefficients as well as Einstein and Debye temperatures for Ba0.73 Ni4 Sb8.1 Sn3.9 and Ba0.95 Ni4 Sb6.1 Sn5.9 . These data were in accordance with the Debye temperatures obtained from the specific heat (4.4 K < T < 140 K) and Mössbauer spectroscopy (10 K < T < 290 K). Rather small atom displacement parameters for the Ba filler atoms indicate a severe reduction in the "rattling behaviour" consistent with the high levels of lattice thermal conductivity. The elastic moduli, collected from Resonant Ultrasonic Spectroscopy ranged from 100 GPa for Ni4 Sb8.2 Sn3.8 to 116 GPa for Ba0.92 Ni4 Sb6.7 Sn5.3 . The thermal expansion coefficients were 11.8 × 10 −6 K −1 for Ni4 Sb8.2 Sn3.8 and 13.8 × 10 −6 K −1 for Ba0.92 Ni4 Sb6.7 Sn5.3 . The room temperature Vickers hardness values vary within the range from 2.6 GPa to 4.7 GPa. Severe plastic deformation via high-pressure torsion was used to introduce nanostructuring; however, the physical properties before and after HPT showed no significant effect on the materials thermoelectric behaviour.